INDEPENDENT LEARNING AS AN IMPORTANT FACTOR IN PERSONAL AND PROFESSIONAL DEVELOPMENT - Sultonova Iroda Shukurullo qizi (Bright Mind Publishing, 2025)
In the modern world, education is not limited to knowledge obtained at school or university. The rapid development of technologies and the growing need for new knowledge encourage people to constantly learn and update their skills. Independent education is one of the important factors of personal and professional development, and is a necessary tool not only for acquiring knowledge, but also for self-development and achieving success in society.
Keywords: Independent learning, personal and professional development, knowledge, modern education.